2019
DOI: 10.15287/afr.2018.1077
|View full text |Cite
|
Sign up to set email alerts
|

Inter-regional beta-diversity patterns of the woody flora of Greece

Abstract: This study aimed to estimate and explain the compositional differentiation and observed beta-diversity (partitioned as turnover and nestedness) patterns of woody species in Greece. Specifically, the 13 phytogeographical regions of Greece were compared at three taxonomic levels: family, genus, and (sub-) species. In Greece, 565 woody taxa have been identified, which are classified into 224 genera and 85 families. Phytogeographical regions were grouped according to their similarity in floristic composition using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…In the present study, we presented the floristic catalogue of all the vascular plant taxa recorded during a botanical survey aimed at investigating the effects of land use change and land abandonment on plant taxonomic and functional diversity, in the floristic region of Northern Pindus. Despite its small surface area, compared to the other floristic regions of mainland Greece, Northern Pindus hosts a high number of plant taxa and a high number of Balkan endemic woody taxa (Xystrakis & al. 2019;Dimopoulos & al.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we presented the floristic catalogue of all the vascular plant taxa recorded during a botanical survey aimed at investigating the effects of land use change and land abandonment on plant taxonomic and functional diversity, in the floristic region of Northern Pindus. Despite its small surface area, compared to the other floristic regions of mainland Greece, Northern Pindus hosts a high number of plant taxa and a high number of Balkan endemic woody taxa (Xystrakis & al. 2019;Dimopoulos & al.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, O'Brien (1993) have demonstrated a similar relationship between woody plant species richness and a climatic gradient in Southern Africa. Xystrakis et al (2019) showed that woody plants diversity was higher along a north-western to southeastern gradient, which was related to a dominant climatic gradient throughout Greece. In China, Qian (2013) showed that woody plant species richness varies greatly along environmental gradients at the regional scale, and climatic variables are important forces driving gradients of species richness.…”
Section: Distribution In Algeriamentioning
confidence: 97%
“…Σύμφωνα με τη διάκριση των Strid and Tan (1997) η Ελλάδα έχει διαιρεθεί σε 13 χλωριδικές φυτογεωγραφικές περιοχές με την περιοχή της Φλώρινας να ανήκει στη Βόρεια και Κεντρική Ελλάδα (North Central Greece, NC) (Dimopoulos et al 2013, Xystrakis et al 2019. Ως συνέπεια της βαθμιαίας, με το υψόμετρο και τις τοπικές εκθέσεις, μεταβολής του τοπικού κλίματος, η περιοχή έρευνας, ανάλογα και με τις ειδικές εδαφικές της συνθήκες και κάτω από την επίδραση της επέμβασης του ανθρώπινου παράγοντα, είναι ιδιαίτερης σημασίας για τη χώρα μας, γιατί μέσα σε αυτήν εντοπίζονται σε ανάπτυξη, εξελικτική ή οπισθοδρομική διαδοχή, οι ακόλουθες φυτοκοινωνικές ζώνες (Αθανασιάδης 1986): Η περιοχή έρευνας "ανήκει σε δύο ζώνες, στην Παραμεσογειακή ζώνη βλάστησης (Quercetalia pubescentis) (Λοφώδης, υποορεινή) και στη Ζώνη Δασών Οξιάς -Ελάτης και ορεινών παραμεσόγειων κωνοφόρων (Fagetalia) (Ορεινή -Υποαλπική)".…”
Section: χλωρίδα και πανίδαunclassified